Assistance with Inventory Management, Warehousing, and Accounts Payable Recording Based on Internal Controls for MSME Aleeta Kopi - Wahyuni; Istianah Hadaming; Umi Fitrah Indah Sari; Marshanda Jufri; Nur Syaqila; Ananta Putra Dampangtiro; Aisyah Ramadhani Basri (Masterpiece, 2026)
Coffee shop micro, small, and medium enterprises (MSMEs) commonly face operational risks arising from poorly managed raw material inventory, unstructured warehousing, and undocumented trade payables to suppliers. This community service activity aimed to assist UMKM Aleeta Kopi in Makassar in strengthening simple internal control over its inventory, warehousing, and trade payable recording cycle. A descriptive qualitative approach was applied through observation, interviews, socialization, hands-on training, independent practice, and joint monitoring and evaluation across six structured sessions. The activity introduced a First In First Out (FIFO)-based stock card, a warehouse labeling and layout system, and a supplier-based trade payable card equipped with due-date tracking. The results show an improvement in the owner's and employees' understanding of basic internal control principles, namely segregation of duties, transaction documentation, and authorization, as well as the successful independent use of the recording tools by the partner. This activity is expected to reduce the risk of stock discrepancies, minimize raw material waste, and improve the accuracy and timeliness of trade payable information at Aleeta Kopi.